The Role Of Digital Culture In Transforming Islamic Da’wah: A Study of Ustadz Adi Hidayat’s Youtube Lecture “Success in Youth According to The Qur’an” - Suwatah, Suwatah; Amriana, Amriana; Kariani, Anjeli Catur; Zahrani, Annisa; Muyaslana, Sultan Muhammad Raihan Putra (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The development of digital technology has significantly transformed religious communication, particularly in Islamic da’wah practices. Digital culture plays an important role in shaping how religious messages are delivered and received by millennial and Generation Z audiences. This study aims to examine the role of digital culture in transforming Islamic da’wah through the YouTube lecture “Success in Youth According to the Qur’an” delivered by Ustadz Adi Hidayat. This research employs a descriptive qualitative approach using library research and content analysis methods. Data were collected through literature review and observation of relevant YouTube videos, focusing on communication strategies, interpretative methods, and audience engagement. The analysis emphasizes how digital media facilitates the integration of Qur’anic interpretation with contemporary communication practices. The findings indicate that digital culture serves as an effective medium for expanding the reach of Islamic da’wah among young audiences. Through the use of digital platforms, Ustadz Adi Hidayat successfully presents Islamic teachings in a systematic, accessible, and engaging manner. The utilization of technology, while maintaining Islamic ethical principles, enhances the relevance and effectiveness of da’wah in the digital era. This study concludes that digital culture is not a barrier to religious propagation but a strategic opportunity for strengthening Islamic values among millennials and young generations.